2012
DOI: 10.1016/j.jad.2011.10.047
|View full text |Cite
|
Sign up to set email alerts
|

The temporal electrocortical profile of emotive facial processing in depressed males and females and healthy controls

Abstract: Background Previous work indicates that emotive processing, such as of facial expressions, may be altered in major depressive disorder (MDD). Individuals with MDD tend to exhibit a mood-congruent processing bias, though MDD may also be characterized by blunted emotive processing in general. Females tend to exhibit enhanced facial emotive processing than males. Few groups have examined temporal electrophysiological event-related potential (ERP)-indexed profiles, spanning preconscious to sustained, conscious pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 68 publications
(105 reference statements)
4
21
0
8
Order By: Relevance
“…Further, the earlier onset of perceiving faces did not lead to faster reactions of children with major depression in the emotional Go/NoGo task. It has to be noted that studies investigating adults with major depression have not reported modulations of N170 latency (Foti et al 2010;Jaworska et al 2012;Maurage et al 2008). So our suggestion is that it may be a developmental feature.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Further, the earlier onset of perceiving faces did not lead to faster reactions of children with major depression in the emotional Go/NoGo task. It has to be noted that studies investigating adults with major depression have not reported modulations of N170 latency (Foti et al 2010;Jaworska et al 2012;Maurage et al 2008). So our suggestion is that it may be a developmental feature.…”
Section: Discussionmentioning
confidence: 70%
“…These modulations in early stages may represent impaired attention that leads to dysfunctional processing at later stages (Yang et al 2011). However, it has to be noted that other investigations have not shown abnormalities in P1 (Foti et al, 2010;Jaworska et al 2012;Maurage et al 2008) and only subtle in P2 (Jaworska et al 2012). …”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…As outlined elsewhere (Jaworska et al, 2012a/b), 53 adults with a primary diagnosis of MDD (Table 1) were assessed. Diagnosis was established by psychiatrists using the Structured Clinical Interview for DSM IV-TR Diagnoses, Axis I, Patient Version (SCID-IV-I/P; First et al, 1997).…”
Section: Methodsmentioning
confidence: 99%